The digital preservation of the Padley Mill as both heritage and knowledge - Ren, Xiang; Doğan, Huriye Armağan (ARSNET, 2024)
Architecture is a form of tacit knowledge in which ideas can be learnt from the past, and that body of tacit knowledge can be recorded in order to give relevant guidance to today's productions. This methodological paper presents a timely reflection that seeks to document the digitisation of Padley Mill in the Grindleford Village of the U.K., which was the key design output and built heritage of the late British academic and architect Peter Blundell Jones. The paper starts with a brief review on the current developments on digital reality capture methods in architectural heritage studies, followed by the Padley Mill digital preservation case study via its three work stages utilising LiDAR data and photogrammetry data. It closes with a humanities echo after the historian-designer on the layering and storytelling of the historic environment. The distinction of this paper is it combines and enhances the digital visualisation and storytelling of endangered architectural heritage through 3D LiDAR scanning and digital photogrammetry, promoting further methodological debates in the digital preservation of architectural heritage.